Potential application of thermo-sensitive hydrogels for controlled release of phenacetin - Ilić-Stojanović Snežana S.; Nikolić Ljubiša B.; Nikolić Vesna D.; Milić Jela R.; Petrović Slobodan D.; Kapor Agneš J.; Nikolić Goran M. (Hemijska Industrija, 2012)
Over the past years, many scientific researches have been focused on thermo-sensitive hydrogels containing N-isopropylacrylamide (NIPAM) as a monomer. The NIPAM based hydrogels with 20 mol% 2-hydroxypropyl methacrylate (HPMet) were synthesized using ethylene glycol dimethacrylate as a cross-linker. The characterization of xerogel and phenacetin using FTIR spectra and SEM micrographs confirm the performed synthesis with satisfactory purity as well as loading of phenacetin into hydrogel. The swelling transport mechanism at simulated physiological conditions (pH 2.20 and 7.40 at 37°C) is described by the time-independent kinetics. The potential application of synthesized hydrogels for the controlled release of phenacetin as a model drug was investigated at simulated physiological conditions by HPLC method. [Acknowledgement. This work is part of the project MNTR TR-34012 financed by the Ministry of Education and Science of the Republic of Serbia. The authors are grateful for the support provided by the Ministry.]